ChemInform Abstract: [2 + 2] Cycloaddition Reactions of Butadienyl Ketene with 1, 4‐Diazabuta‐1, 3‐dienes: Synthesis of Functionalized Butadienyl‐4‐iminomethyl‐azetidin‐2‐ones and Butenylidene‐butadienyl‐[2, 2′‐biazetidine]‐4, 4′‐diones. Issue 52 (6th December 2016) - Bains, Deepak; Kumar, Yogesh; Singh, Prabhpreet; Bhargava, Gaurav
Abstract: The reactions of in situ‐generated butadienylketene with 1, 4‐diazabuta‐1, 3‐dienes are studied.